THE ROLE OF PERCEIVED USEFULNESS AND PERCEIVED EASE OF USE ON USAGE DECISION IN THE GOSEH APPLICATION THROUGH TRUST AS AN INTERVENING VARIABLE (Case Study in the Community in Berastagi District) - Arianty, Nel; Munthe, Nindi Palensia br (Proceeding International Seminar of Islamic Studies, 2024)
This research aims to determine and analyze the influence of perceived usefulness and perceived ease of use on the decision to use the Goseh application through trust as an intervening variable (case study in the community in Berastagi subdistrict). The sample used was non-probability sampling with a total of 96 respondents. The data collection technique uses an online questionnaire with a Likert measurement scale. Data analysis techniques use Path Analysis, Partial Least Square (PLS) and Hypothesis Testing. Data processing in this research uses SmartPLS and SPSS software programs. The results of this research are that perceived usefulness has a positive and significant influence on trust, perceived ease of use has a positive and significant influence on trust, perceived usefulness has a positive and significant influence on usage decisions, perceived ease of use has a positive and significant influence on usage decisions, trust has a positive influence and significant on usage decisions, perceived usefulness has a positive and significant effect on usage decisions with trust as an intervening variable and perceived ease of use has a positive and significant effect on usage decisions with trust as an intervening variable.